Wealth, Office and Rank in Roman Italy - Danon, Bart (Cambridge University Press, 2026)
Dismantles the simplistic equation of wealth, political power and social rank in the Roman Empire. Adopts an innovative approach which combines economic modelling with archaeological and epigraphic evidence, providing fresh perspectives on the complexities of wealth and power. This title is also available as Open Access on Cambridge Core.